Evaluation of the impact of vitamin D on blood pressure in patients with diabetes mellitus - Muhammad Khalif Alghifari; Mira Delima Asikin; Sari Eka Pratiwi; Suriadi Jais (Healthcare in Low-resource Settings)
This study assessed the effects of vitamin D on blood pressure in individuals diagnosed with diabetes mellitus. Convenience sampling and a cross-sectional, analytical, quantitative approach were used. Blood samples were collected and analysed by a designated laboratory officer to measure vitamin D levels. Twenty-eight (70%) women, 18 (45%) housewives with a median age of 52 (36-60), median systole of 143.5 (102–180), and median diastole of 80 years (range, 59–110 years). Thirty-five (87.5%) had fasting blood glucose over 140 mg/dl, and 33 (82.5%) postprandial more than 100 mg/dl. The predictive validity test showed that a systole cut-off score of 160–179 yielded sensitivity, specificity, LR+, and LR– (81%, 67%, 2.4, and 0.3). Systole had a LR+ of 2.4 and was a moderate diagnostic test. Diastole cut-off score of 90–99 produced sensitivity, specificity, LR+, and LR– (84%, 67%, 2.5, and 0.2). The ROC for systole was AUC 0.65 (95% CI: 0.49–0.80) and diastole had AUC 0.67 (95% CI: 0.50–0.81). Patients with diabetes and hypertension were found to have vitamin D levels <30 ng/mL.